Perbedaan gender mengenai kepuasan pernikahan pada individu yang menikah dengan adat Nyentana di Bali - Permata Jati, Ni Made Karinadevi; Hartanti, Hartanti (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
The traditional marriage of Nyentana is a unique Balinese marriage tradition to oppose the commonly held, patriarchal marriage tradition by emphasizing the primary position of female. This research set out to determine whether there exists a significant difference in marital satisfaction between women and men who were married as according to the traditional marriage of Nyentana in Balinese culture. Seventy three individuals aged 20–40 years (M = 30; SD = 5.5) who performed Nyentana marriage participated in this study. Participants responded to Nyentana ENRICH Marital Satisfaction Scale, which had been adapted into Indonesian Language. Open-ended questions were also administered for supplementary analysis. The results showed that there was no significant gender differences among individuals who were married with Nyentana tradition. Marriage satisfaction in the two groups of subjects was categorized as high. The high level of marriage satisfaction among individuals involved in Nyentana traditional marriage were caused by their strong cultural belief about the merits of its tradition to carry on the family lineage, by good partner communication, and by the proportional involvement between genders in household decision making.